The Effectiveness Of Using English Songs To Teach Listening Skill of the Senior High Students in Samarinda - Maria Ulfa (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2021)
English is the one of the international languages which taught and learned in Indonesia as a foreign language. English skills are dividedinto 4 skills that the students need to be mastered. There are speaking, reading, writing, and listening. Listening is an important skill becauseit can make someone knowsomething in English properly. Students have problems when they listen to the native speakers. A bad listening skill of Senior High School students made the researcher took listening skill and then tried the English songs to teach the students to solve the problems they got when they learned listening skill in the class. The research design of this research is experimental research. The population is the tenth grade students of SMAN 2 Samarinda and the sampling technique in this research used simple random sampling. To collect the data the researcher conducted the pre-test and post-test to know about the score of listening test. To analyse the data the researcher used t-test formula. The research objective was to find out whether there waseffective or not for the students who have been taught by using English songs. The researcher used two classes for control class and experiment class. The sample of this research was X Language and Culture and X Social 3 at SMA Negeri 2 Samarinda.The instrument of the research is the listening test, there is fill in the blank test. In analyzing the data, it used repeated measure t-test in which significance level 5% with d.f. = Pairs – 1. The result of the research showed that mean score in pretest of the students’ in experiment class was 52,78 and the mean score of the students’ in control class was 59,89. While the mean score in posttest of the students’ in experiment class 76,17 and the students’ in control class was 54,50. The result also showed that there was a significant difference of the mean score. It had increased about 23,39 in experiment class after treatments. The result of tcount was 24,767 with significant level 5% with d.f. = Pairs – 1.It was found t- table = 2,030.Because of thet-calculated>t-table, so it could be concluded that there was significant. So, the Alternative Hypothesis (Ha) in this research is accepted. In conclusion, it can be said that English songs is effective to teach listening skill.